Maintenance Management Systems in the Czech Enterprises of Chemical and Food Industries - Branska, Lenka; Pecinova, Zuzana; Patak, Michal; Stankova, Monika; Kholova, Pavla (Vysoké učení technické v Brně, Fakulta podnikatelská, 2016)
The aim of this article is to use the results of the qualitative research to describe the current form of maintenance systems used in enterprises of chemical and food industries, and then to discuss and generalize the results. The main objective of the research in individual companies was to determine how they perform the strategic and tactical operational planning of maintenance, implementation of these plans and their control. Qualitative primary research has shown that production equipment maintenance systems are irreplaceable in chemical and food industry enterprises, but there is great potential for improvement. Improvement should be focused on the area of strategic as well as tactical and operational planning of production equipment maintenance. In terms of strategy, the biggest opportunity for a dramatic improvement is the implementation of modern maintenance methods. In the context of the existing systems, improvement can be achieved especially in setting strategic objectives, the system of indicators to measure the performance of maintenance and in implementing an information system. In the tactical and operational level, it would be useful to develop a maintenance planning system linked with suppliers and customers and utilize mathematical methods and models to optimize plans for this business activity.
Keywords: maintenance; maintenance systems; production equipment; chemical industry; food industry